2003
DOI: 10.1177/004947550303300322
|View full text |Cite
|
Sign up to set email alerts
|

Dyspepsia: Endoscopy Findings in Uganda

Abstract: Lacor hospital, a mission hospital with a bed capacity of 460, serves the population of northern Uganda--other hospitals in the area use it as a referral hospital. The study was conducted in the endoscopy unit from November 1999 to 31 August 2000. The department of surgery runs the endoscopy unit with the surgeon heading the endoscopy team. Routine diagnostic and therapeutic endoscopy is carried out weekly for elective cases, and emergency service is as and when required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…As a result, it is 29% in Canada [4], 44.1% in the US [5], 38% in the United Kindom [6], 25% in France [7]. In Africa, particularly in Uganda and in Benin, it represents respectively 72% and 77.9% of upper gastrointestinal endoscopy indications in the general population [8] [9].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, it is 29% in Canada [4], 44.1% in the US [5], 38% in the United Kindom [6], 25% in France [7]. In Africa, particularly in Uganda and in Benin, it represents respectively 72% and 77.9% of upper gastrointestinal endoscopy indications in the general population [8] [9].…”
Section: Introductionmentioning
confidence: 99%
“…In one study in western Uganda, the majority of dyspeptic patients had gastritis [6] while in a study done in Kenya a significant majority had functional dyspepsia [7], contrasting with a study in Nigeria where only 8 % of the participants had functional dyspepsia [8]. Other studies conducted in Uganda are representative of specific regions [9] and therefore non-generalizable. This variability in findings, therefore, warrants a characterization of dyspepsia in Uganda at a national referral center that receives a more diverse patient population from all regions in Uganda.…”
Section: Resultsmentioning
confidence: 99%
“…These prevalence rates were much lower than the 38.7% reported by Ndububa et al[37] for the years 1992-1999 at the same institution. In Uganda, two separate cross-sectional studies also showed reduction in DU prevalence from 18% in 2005[38] to 3.8% in 2014[39].…”
Section: Patterns Of Peptic Ulcer Disease In Africamentioning
confidence: 99%